КЕЧИРИМЛИЛИК ВА БАҒРИКЕНГЛИК ФАЗИЛАТИ ОЛИЙ ҚАДРИЯТ СИФАТИДА - Жуманазарова, Д.У. (SCIENCE and SOCIETY, 2016)
The article deals with the study of such human qualities as forgiveness, tolerance, love and indulgence to children-orphans. These qualities have been analysed on the background of historical events and political situation in our country.